Women’s rights in the workplace – EU vs. Spanish legislation on co-responsibility rights - Isabel Ribes Moreno (Stanovništvo)
The establishment of a regulatory framework to ensure women’s equality in the workplace has been a lengthy journey in the European Union (EU) and its Member States. In Spain, there was no significant impetus initially. Nevertheless, a few decades later, due to substantial legislative improvement, Spain is considered by many a very convenient place for women to live and work, even though there is still much to be done. This article aims to analyse the adequacy of Spanish labour regulations with the EU’s normative acquis concerning work-life balance and co-responsibility—essential elements for the achievement of equality in the workplace. To this end, detailed reference will be made to the introduction of rights through the domestic regulatory framework. Consequently, the study will assess whether Spain is one of the EU countries with the highest standards of gender equality in employment and occupation resulting from the implementation and exercise of work-life balance rights to achieve co-responsibility and resolve reconciliation issues.